2020
DOI: 10.3390/suschem1020009
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxymethylfurfural Hydrodeoxygenation to 2,5-Dimethylfuran in Continuous-Flow System over Ni on Nitrogen-Doped Carbon

Abstract: Waste lignocellulosic biomass is sustainable and an alternative feedstock to fossil resources. Among the lignocellulosic derived compounds, 2,5-dimethylfuran (DMF) is a promising building block for chemicals, e.g., p-xylene, and a valuable biofuel. DMF can be obtained from 5-hydroxymethylfurfural (HMF) via catalytic deoxygenation using non-noble metals such as Ni in the presence of H2. Herein, we present the synthesis of DMF from HMF using 35 wt.% Ni on nitrogen-doped carbon pellets (35Ni/NDC) as a catalyst in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The liquid-phase LS depolymerization using water/alcohols solvent mixtures was conducted in a continuous flow fixed bed reactor, similar to our previously described system (Figure S2 in ESI). [68][69][70] This system consists of: (A) an HPLC pump equipped with a pressure sensor (Knauer Azura P 4.1S Series), (B) a mass-flow controller to supply a specific H 2 flow (Model SLA58050 from Brooks), (C) T-piece for gas-liquid mixer (Swagelok SS-400-30) to mix the supplied H 2 with the reaction solution before reaching the pre-heating unit and the catalyst bed (D) a two-side opened heating unit equipped with a heat controller (D) a two-side opened heating unit equipped with a heat controller (Model # 4848 from Parr Instrument Company), (E) a sampling unit equipped with proportional relief valves also used as a pressure regulator (Swagelok SS-RL4M8F8-EP), cf., Figure S2 in ESI. To ensure efficient heating, a cylindrical aluminium adapter with three boreholes was matched inside the heating unit.…”
Section: Continuous Flow Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The liquid-phase LS depolymerization using water/alcohols solvent mixtures was conducted in a continuous flow fixed bed reactor, similar to our previously described system (Figure S2 in ESI). [68][69][70] This system consists of: (A) an HPLC pump equipped with a pressure sensor (Knauer Azura P 4.1S Series), (B) a mass-flow controller to supply a specific H 2 flow (Model SLA58050 from Brooks), (C) T-piece for gas-liquid mixer (Swagelok SS-400-30) to mix the supplied H 2 with the reaction solution before reaching the pre-heating unit and the catalyst bed (D) a two-side opened heating unit equipped with a heat controller (D) a two-side opened heating unit equipped with a heat controller (Model # 4848 from Parr Instrument Company), (E) a sampling unit equipped with proportional relief valves also used as a pressure regulator (Swagelok SS-RL4M8F8-EP), cf., Figure S2 in ESI. To ensure efficient heating, a cylindrical aluminium adapter with three boreholes was matched inside the heating unit.…”
Section: Continuous Flow Setupmentioning
confidence: 99%
“…Furthermore, the latter step was coupled to hydrogenolysis/hydrogenation fragmentation (SHF) in a continuous flow system using water/alcohol solvent and 35 wt.-% Ni supported on NDC as a catalyst. 68,69 Finally, the advantage of operating the catalytic depolymerization of LS in a continuous flow system is highlighted with respect to batch system.…”
Section: Introductionmentioning
confidence: 99%
“…[ 45–48 ] Certainly, this numbers showed that there is a great potential for the isomer‐pure synthesis of p XL as a premonomer from renewable resources. In this context, there are reported studies for the synthesis of p XL from biomass‐derived 2,5‐dimethylfuran (DMF), [ 49 ] which involves a Diels‐Alder cycloaddition of ethylene to form the intermediate 1,4 dimethyl‐7‐oxabicyclo[2.2.1] hept‐2‐ene, followed by a dehydration step to p XL using different types of zeolites as a catalyst. [ 45–48,50–52 ] For this reaction usually batch systems are used, combined with high reaction temperature (523–623 K), high ethylene pressure (5.0–7.0 MPa) and long reaction times (24–48 h).…”
Section: P‐xylene From 25‐dimethylfuranmentioning
confidence: 99%
“…[8][9][10] Typically, a biomass heterogeneously-catalyzed hydrogenation reaction is conducted using relatively high temperature (100-200 C), external pressurized H 2 as reductive agent and supported metals as catalyst, such as Pt, Pd, Ru and Ni. 8,9,[11][12][13][14] Heterogeneous catalysis is the preferred method because it allows for the implementation of more economically efficient and environmentally benign reactor designs. However, bio-renery processes are expensive when compared to traditional reneries.…”
Section: Introductionmentioning
confidence: 99%